Pelatihan Kepemimpinan Militer Resimen Mahasiswa Unissula - Sulchan, Ahmad; Listyawati, Peni Rinda; Ismail, Munaf (Indonesian Journal of Community Services, 2025)
Menwa (Resimen Mahasiswa) yang akhir-akhir ini kurang peminatnya perlu sekali digalakkan keberadaannya untuk menjadi generasi yang handal karena merupakan komponen cadangan dalam pertahanan Negara Indonesia. Program pengabdian masyarakat yang dilaksanakan oleh tim pengabdian kepada masyarakat Fakultas Hukum Unissula bekerja sama dengan Resimen Mahasiswa Unissula bertujuan untuk meningkatkan pengetahuan dan ketrampilan tentang kepemimpinan generasi muda. Peserta pelatihan adalah  Camen (Calon Resimen) dan Anggota Menwa serta Alumni Menwa yang tergabung dalam IARMI (Ikatan Alumni Resimen Mahasiswa Indonesia) Unissula serta Menwa dari Perguruan Tinggi yang ada di Kota Semarang. Metode pelaksanaan yang digunakan dalam pengabdian ini adalah, pelatihan, penyuluhan dan pendampingan. Hasil evaluasi pengabdian menunjukkan antusiasme dari peserta sangat tinggi, hal ini dapat dilihat dari banyaknya peserta yang ikut hadir dan mengajukan pertanyaan-pertanyaan. Sehingga dari hasil pengamatan, diskusi dan tanya-jawab selama kegiatan PKM (Pengabdian Kepada Masyarakat) berlangsung, dapat diketahui adanya peningkatkan pengetahuan dan kemampuan peserta dalam pelatihan kepemimpinan militer resimen mahasiswa yang mengedepankan disiplin berwawasan kebangsaan dan cinta tanah air.Menwa (Student Regiment), which has recently been lacking in interest, needs to be encouraged to become a reliable generation because it is a reserve component in the defense of the Indonesian State. The community service program implemented by the Unissula Faculty of Law community service team in collaboration with the Unissula Student Regiment aims to improve the knowledge and skills of leadership of the younger generation. Training participants are Camen (Prospective Regiment) and Menwa Members as well as Menwa Alumni who are members of IARMI (Indonesian Student Regiment Alumni Association) Unissula as well as Menwa from Universities in the City of Semarang. The implementation method used in this service is training, counseling and mentoring. The results of the service evaluation show that the enthusiasm of the participants is very high, this can be seen from the large number of participants who attended and asked questions. Thus, from the results of observations, discussions and questions and answers during the PKM (Community Service) activities, it can be seen that there is an increase in the knowledge and abilities of participants in the military leadership training of the student regiment which prioritizes discipline with a national perspective and love for the homeland.